1974
DOI: 10.1113/jphysiol.1974.sp010618
|View full text |Cite
|
Sign up to set email alerts
|

Properties of rarely encountered types of ganglion cells in the cat's retina and on overall classification

Abstract: SUMMARY1. In a reference sample of 960 cat retinal ganglion cells, seventy-three had receptive fields departing from the concentric centre-surround pattern.2. Five classes were distinguished among the subset: local edge detectors, direction-selective cells, colour-coded cells, uniformity detectors, edge inhibitory off-centre cells.3. Local edge detectors (forty-five) possessed a radially symmetrical pattern of responses to both centrifugal and centripetal movements of both black and white small targets, an on-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
136
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 376 publications
(153 citation statements)
references
References 41 publications
16
136
1
Order By: Relevance
“…Moving a visual stimulus, say a dark bar on a light background, in a particular, the preferred, direction elicits a vigorous response from the cell while movement in the opposite direction, termed null direction, yields no significant response (figure 3d). Directional selective cells, described in the frog's retina in a classical paper by Maturana, Lettvin, McCulloch and Pitts ( 1960), have subsequently been identified, among others, in the third optic ganglion of the house fly, the retina of the rabbit, squirrel and cat, the optic tectum of frogs and pigeons and the visual cortex of both cats and monkeys (Hassenstein and Reichardt, 1956;Maturana and Frenk, 1963;Barlow and Levick, 1965;Rubel and Wiesel, 1962;Cleland and Levick, 1974;Hausen, 1981).…”
Section: Direction Selectivitymentioning
confidence: 99%
“…Moving a visual stimulus, say a dark bar on a light background, in a particular, the preferred, direction elicits a vigorous response from the cell while movement in the opposite direction, termed null direction, yields no significant response (figure 3d). Directional selective cells, described in the frog's retina in a classical paper by Maturana, Lettvin, McCulloch and Pitts ( 1960), have subsequently been identified, among others, in the third optic ganglion of the house fly, the retina of the rabbit, squirrel and cat, the optic tectum of frogs and pigeons and the visual cortex of both cats and monkeys (Hassenstein and Reichardt, 1956;Maturana and Frenk, 1963;Barlow and Levick, 1965;Rubel and Wiesel, 1962;Cleland and Levick, 1974;Hausen, 1981).…”
Section: Direction Selectivitymentioning
confidence: 99%
“…The fact that blue-ON cells responded preferentially to the same stimulus that minimized the responses of achromatic cells, demonstrates that S-cone stimuli were effective in driving a second receptor mechanism. It has been known since early studies of the cat visual system (Daw and Pearlman, 1970;Cleland and Levick, 1974;Wilson et al, 1976;Krüger, 1979;Rowe and Cox, 1993) that certain "colorcoded" retinal ganglion cells or thalamic relay cells respond vigorously to narrow-band blue light but are inhibited by longer wavelengths. Together, 13 examples of color-coded neurons are known from earlier studies of the cat LGN (Daw and Pearlman, 1970;Pearlman and Daw, 1970;Cleland et al, 1976;Wilson et al, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the few examples of color-coded neurons known from studies done in cats (Daw and Pearlman, 1970;Cleland and Levick, 1974;Wilson et al, 1976) showed mostly ON responses to blue light. Simple ON-OFF flashes (square-wave modulation) of S-cone contrast evoked typically tonic ON responses in our sample of 14 blue-ON cells (Fig.…”
Section: Sign and Weight Of The S-cone Inputmentioning
confidence: 99%
See 2 more Smart Citations